2017
DOI: 10.1186/s40795-016-0121-3
|View full text |Cite
|
Sign up to set email alerts
|

Higher bioavailability of magnesium citrate as compared to magnesium oxide shown by evaluation of urinary excretion and serum levels after single-dose administration in a randomized cross-over study

Abstract: Higher bioavailability of magnesium citrate as compared to magnesium oxide shown by evaluation of urinary excretion and serum levels after single-dose administration in a randomized cross-over study AbstractBackground: The development of several disorders, such as cardiovascular diseases, diabetes and osteoporosis, has been linked to suboptimal dietary magnesium (Mg) intake. In this context, a number of studies have tried to investigate which Mg compounds are best suited for Mg supplementation. Results sugges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 13 publications
(19 reference statements)
1
25
0
1
Order By: Relevance
“…Several chemical balance studies investigating urinary Mg 2+ excretion in humans found no significant differences between various Mg 2+ salts, including the comparison of organic with inorganic Mg 2+ salts [ 108 - 120 ], which indicated that all types of Mg 2+ are suitable to maintain or restore the Mg 2+ status. Some other studies observed a slightly better bioavailability of organic Mg 2+ salts under standardized conditions [ 112 - 116 ].…”
Section: Data On Intestinal Mg2+ Absorptionmentioning
confidence: 96%
See 3 more Smart Citations
“…Several chemical balance studies investigating urinary Mg 2+ excretion in humans found no significant differences between various Mg 2+ salts, including the comparison of organic with inorganic Mg 2+ salts [ 108 - 120 ], which indicated that all types of Mg 2+ are suitable to maintain or restore the Mg 2+ status. Some other studies observed a slightly better bioavailability of organic Mg 2+ salts under standardized conditions [ 112 - 116 ].…”
Section: Data On Intestinal Mg2+ Absorptionmentioning
confidence: 96%
“…Likewise, a product study by Kappeler et al . (2017) observed a slightly higher bioavailability of Mg 2+ citrate as compared to Mg 2+ oxide using 24-h urinary Mg 2+ excretion as biomarker [ 116 ]. However, the difference in urinary Mg 2+ levels between Mg 2+ citrate (7.2±1.48 mmol) and Mg 2+ oxide (6.7±1.43 mmol)-although statistically significant-is marginal.…”
Section: Data On Intestinal Mg2+ Absorptionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, Crews' conditions were scarcely efficient for studying Mg bioaccessibility. According to the literature, Mg bioaccessibility may be influenced by the compound used in the diet; the ingestion of citrate was more efficient that oxide [20]. Mg absorption in healthy women is reported to be incremental (11-14%) when mineral water was consumed alone or in combination with meals [21].…”
Section: Effect Of Diverse Factors On the Mineral Bioaccessibilitymentioning
confidence: 99%